Assessment of Mothers Practice among Using Oral Rehydration Solution for Their Children with Diarrhea in Kerbala Pediatric Teaching Hospital - Sabah Musihb, Zeki; Saadoon Oleiwi, Sajidah; Makee Mahmood, Fatma (International Journal of Psychosocial Rehabilitation, 2020)
Diarrhea continues to pose a great threat to children under the age of five, especially in third-world countries or countries that suffer from the ravages of recurrent wars, including Iraq, as this affects the quality of health services provided to patients, especially children. The inhabitants of Karbala are unstable (and differ greatly) during the months of the year because it is a holy city that millions of Muslims visit during the season of visiting the holy shrines, so the number of children who are exposed to diarrhea increases.Objectives: The present study aimed to evaluate mothers' practices on the use of oral rehydration solution, find out demographic characteristics of mothers like age, level of education, occupation, and resident area, and the demographic characteristics of the children in relation to age, gender, arrangement of the child among family members, and the type of feeding.Methodology: descriptive study, conducted at Karbala Teaching Hospital for Children, from the period of December (2016) to the end of February (2017). The non-probability sample consists of 100 mothers as a direct from Karbala Teaching Hospital for Children, using a questionnaire prepared for this purpose. . Results: The results show that (64%) of mothers their age between (20-30) years, (56%) of mothers graduate from primary school, and (93%) of mothers were unemployed. The results also show that (62%) of mothers prepared ORT by 1 litter of boiled, cooled water, and (56%) of mothers gave to the child rice water with salt during ORT.Recommendations: The researchers recommended the necessity of instruction and implementing a special educational program for mothers on how to care for children suffering from diarrhea.Conclusion: Diarrhea is the most common health problem among children, especially those under five years of age, leading to admission to the Karbala Teaching Hospital for Children in this period.